2017
DOI: 10.1186/s12872-017-0486-5
|View full text |Cite
|
Sign up to set email alerts
|

Does improvement in self-management skills predict improvement in quality of life and depressive symptoms? A prospective study in patients with heart failure up to one year after self-management education

Abstract: Background: Heart failure (HF) patient education aims to foster patients' self-management skills. These are assumed to bring about, in turn, improvements in distal outcomes such as quality of life. The purpose of this study was to test the hypothesis that change in self-reported self-management skills observed after participation in self-management education predicts changes in physical and mental quality of life and depressive symptoms up to one year thereafter. Methods: The sample comprised 342 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
0
20
1
1
Order By: Relevance
“…Studies in diabetic patients and those with chronic heart failure have reported improved not only patient self-reported health, satisfaction, and quality of life but also better patient survival. [2][3][4][5] There have been few studies investigating self-care during hemodialysis and shared the responsibility of care. However, these limited studies have suggested that self-care during hemodialysis improved physical functioning, and greater knowledge of kidney disease and treatment improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in diabetic patients and those with chronic heart failure have reported improved not only patient self-reported health, satisfaction, and quality of life but also better patient survival. [2][3][4][5] There have been few studies investigating self-care during hemodialysis and shared the responsibility of care. However, these limited studies have suggested that self-care during hemodialysis improved physical functioning, and greater knowledge of kidney disease and treatment improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, patients with chronic ill-health conditions frequently report relatively high levels of self-reported depression. 12 Self-help in HD is typically associated with home dialysis therapies, and as such the improvement in patient outcomes reported, 13 may be biased by patient selection. 4 A number of psychological theories, including human becoming theory, Bandura's self-efficacy theory, and Orem's self-care model, [5][6][7] have suggested that patients who take greater care of their own medical care have less depression and are more motivated to perform and promote activities designed to maintain or improve health care.…”
Section: Introductionmentioning
confidence: 99%
“…4 A number of psychological theories, including human becoming theory, Bandura's self-efficacy theory, and Orem's self-care model, [5][6][7] have suggested that patients who take greater care of their own medical care have less depression and are more motivated to perform and promote activities designed to maintain or improve health care. 8 Indeed, studies in other chronic healthcare conditions, diabetes mellitus and congestive heart failure have reported that patients who take greater control of their own medical care [9][10][11][12] reported a reduction in emotional burden, 9 short-term improvement in glycaemic control, 10 over-all quality of life, 11 and shortterm changes in self-reported self-management skills predicted intermediate-term changes in improved mental quality of life and long-term changes in better physical quality of life. 12 Self-help in HD is typically associated with home dialysis therapies, and as such the improvement in patient outcomes reported, 13 may be biased by patient selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-management interventions are one option for advancing improved HCV knowledge and health-related quality of life (HRQOL). (20,21) It is now well established that HCV is of universal importance, affecting all countries, leading to a major global health problem that requires widespread active interventions for its prevention and control (22) . Education is the cornerstone supporting the framework of self-management programs that teach patients to identify and prioritize their own problems, take appropriate action, and enlist the support needed to solve these problems in collaboration with health care providers and family.…”
Section: Introductionmentioning
confidence: 99%